2018
DOI: 10.1016/j.cbpc.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

The neurological toxicity of heavy metals: A fish perspective

Abstract: The causes of neurodegenerative diseases are complex with likely contributions from genetic susceptibility and environmental exposures over an organism's lifetime. In this review, we examine the role that aquatic models, especially zebrafish, have played in the elucidation of mechanisms of heavy metal toxicity and nervous system function over the last decade. Focus is applied to cadmium, lead, and mercury as significant contributors to central nervous system morbidity, and the application of numerous transgeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(42 citation statements)
references
References 120 publications
0
41
0
1
Order By: Relevance
“…Casein 1 27.0 Fish meal 2 32.0 Wheat flour 3 18.0 Dextrin 1 4.20 Corn starch 2 3.50 Fish oil 4 6.10 Vitamin premix 5 3.00 Mineral premix 6 3.00 Cellulose 1 3.20 Hg-premix (5000 ppm) 0.00…”
Section: Ingredients % In Dietmentioning
confidence: 99%
See 1 more Smart Citation
“…Casein 1 27.0 Fish meal 2 32.0 Wheat flour 3 18.0 Dextrin 1 4.20 Corn starch 2 3.50 Fish oil 4 6.10 Vitamin premix 5 3.00 Mineral premix 6 3.00 Cellulose 1 3.20 Hg-premix (5000 ppm) 0.00…”
Section: Ingredients % In Dietmentioning
confidence: 99%
“…All forms of mercury are toxic [4], and organic MeHg is neurotoxic compared to inorganic HgCl 2 in fish [5]. Although mercury is a naturally occurring element, human or anthropogenic activities, particularly through industrial processes, have led to widespread distribution of toxic mercurial derivatives throughout the biosphere [6]. In aquatic conditions, the natural mercury is biologically transformed into organic mercury by different types of microorganisms, basically anaerobic bacteria [7].…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals can accumulate in various organs, including the liver, heart, kidney, and brain, and greatly affect their function. In the last few decades, the presence of neurological damage following acute and chronic exposure to heavy metals has been increasingly evident [90,91]. In particular, it has been shown that the accumulation of some metals can alter the process of myelination, possibly leading to neurodegeneration [92,93].…”
Section: Intake Of Heavy Metals and Oligodendrocytesmentioning
confidence: 99%
“…In fact, it affects almost all tissues and organ systems, such as the respiratory, hematopoietic, renal, cardiovascular, urinary, and urogenital systems, as well as bones [ 2 , 3 , 4 , 5 ]. Moreover, apart from its widely characterized effects in humans [ 4 , 5 , 6 , 7 , 8 ] and animals [ 3 ], the detrimental effects of Pb on the physiology of plants [ 9 ] and fish [ 10 , 11 , 12 ] have also been well-documented.…”
Section: Introductionmentioning
confidence: 99%